Dental caries experience and associated factors in adults: a cross-sectional community survey within Ethiopia - Birke Bogale; Fasikawit Engida; Charlotte Hanlon; Martin J. Prince; Jennifer E. Gallagher (BMC, 2021)
Abstract Background Ethiopia is a developing sub-Saharan African country with increasing prevalence of non-communicable diseases (NCDs), including oral conditions. Oral health and dental care have been given little consideration, and there is limited information relating to population oral health and use of dental services in the country. The aim of this study was to examine the burden and associated factors of dental caries experience and investigate access to dental care amongst adults within Ethiopia. Methods This community-based oral health survey is a baseline study for the ASSET - Health System Strengthening in sub-Saharan Africa project undertaken in the Butajira area, south-central Ethiopia. A stratified random sample of households and individuals participated in the study. The survey instruments were mainly based on the WHO Oral Health Survey Methods manual (5th ed.). Face-to-face interviews and clinical dental examinations were conducted. The data were analysed for descriptive statistics; and Poisson regression models were built to assess the association of dental caries and predictor variables in adults (≥18 years). Results Most of the study population (n = 626) were female (63.9%), married (71.4%) and Muslim (76.0%). Just over half (53.2%) lived in rural areas and many (44.4%) had no formal education. A majority (74.0%) reported never utilising dental care services, and the main reason was never experiencing any dental problem (71.3%). Sixty percent (n = 377) of the adults had experienced dental caries, 88.0% (n = 332) of whom had untreated carious teeth. Pain or discomfort was reported by 16.5, and 7.2% had one or more PUFA component. Most (59.9%) adults with dental caries experience reported tooth pain or discomfort during the last year. In the fully adjusted Poisson regression model, increasing age, dental care utilisation and Khat chewing had positive significant associations with dental caries experience, whilst education status was negatively associated (p < 0.05). Conclusion This study demonstrated a high burden of dental caries and considerable consequences resulting from untreated disease in this population of adults. There was evidence of social inequity, limited utilisation of dental care and oral health awareness. This highlights the need for oral health system strengthening focusing on health promotion and expanding overall access to care.